Different strokes for different folks: Generational differences, social salience, and social performance. (August 2019) - Cox, Kevin C; Stewart, Steve A; Lortie, Jason; Barreto, Tais S
Empirical evidence establishes that entrepreneurs pursue and achieve different goals and objectives with their ventures ranging from purely economic to purely social (e.g. non-profits) in nature. The reason that individual entrepreneurs choose to pursue such divergent paths is currently poorly understood, however. We employ a perspective integrating generational theory, goal-setting theory and the theory of planned behaviour to determine why entrepreneurs of different ages pursue social performance in their ventures. Using a sample of 150 entrepreneurs belonging to Baby Boomer, Generation X and Millennial generations, we examined the relationship between age, social salience and the social performance of their firms. Findings suggest a mediated relationship between age, social salience and social performance.